Perumusan Corrective Action and Preventive Action (CAPA) pada Salah Satu Pedagang Besar Farmasi di Kota Bandung - Ella Fazila; Norisca Aliza Putriana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Pharmaceutical Wholesalers or commonly known as PBFs are companies in the form of legal entities that have permits to procure, store and distribute large quantities of pharmaceutical supplies in accordance with the provisions of applicable laws and regulations. PBF must implement a quality system that includes quality risk management principles. An effective quality management system must include a Corrective Action and Preventive Action (CAPA) process to address deviations and prevent the same problems from occurring again in the future. The research was carried out by reviewing cases found by the Center for Food and Drug Monitoring (BBPOM) at PBF